Patient-prosthesis mismatch following aortic valve replacement - Bilkhu, Rajdeep; Jahangiri, Marjan; Otto, Catherine M (Heart (British Cardiac Society), 2019)
Patient-prosthesis mismatch (PPM) occurs when an implanted prosthetic valve is too small for the patient; severe PPM is defined as an indexed effective orifice area (iEOA) <0.65 cm 2 /m 2 following aortic valve replacement (AVR). This review examines articles from the past 10 years addressing the prevalence, outcomes and options for prevention and treatment of PPM after AVR. Prevalence of PPM ranges from 8% to almost 80% in individual studies. PPM is thought to have an impact on mortality, mainly in patients with severe PPM, although severe PPM accounts for only 10–15% of cases. Outcomes of patients with moderate PPM are not significantly different to those without PPM. PPM is associated with higher rates of perioperative stroke and renal failure and lack of left ventricular mass regression. Predictors include female sex, older age, hypertension, diabetes, renal failure and higher surgical risk score. PPM may be a marker of comorbidity rather than a risk factor for adverse outcomes. PPM should be suspected in patients with persistent cardiac symptoms after AVR when there is high prosthetic valve velocity or gradient and a small calculated effective orifice area. After exclusion of other causes of increased transvalvular gradient, re-intervention may be considered if symptoms persist and are unresponsive to medical therapy. However, this decision needs to consider the available options to relieve PPM and whether expected benefits justify the risk of intervention. The only effective intervention is redo surgery with implantation of a larger valve and/or annular enlargement. Therefore, focus needs to be on prevention.